Chaplin's America - Jourdren, Morgane (Presses universitaires de Rennes, 2026)
Undoubtedly, there is a subversive side to Chaplin’s work. Some scenes are apt to be considered as signs of Chaplin’s intention to ridicule mainstream American society and debunk the myth of American exceptionalism. However, historical and political approaches do not really account for the complexity and the depth of Chaplin’s work. Ironically enough, Chaplin’s films may well be not so much about the American Dream as about a dream of another kind, less tangible and more ethereal. Far beyond the socio-economic or comic aspects it is traditionally associated with, there emerges from Chaplin’s work a more philosophical and metaphysical dimension, a genuine Weltanschauung. God, if He has ever existed, is at best an absentee Landlord and yet, in the midst of universal chaos, there still arises a dream of that remnant of Terra Incognita within all of us, which takes on the colors of a prelapsarian world free from the contradictions of existence here below.